Passive electroculture using copper rods does not improve yield in home container vegetable gardening. - Mya Chier; Aidan Oakey; Michelle L Budny; Nathan P Lemoine (PLoS ONE)
Electroculture, or the practice of applying electric fields or current to plants, has been explored for nearly three hundred years. Recently, home gardeners on social media have adopted the term electroculture to describe inserting copper-wrapped dowels into root soil as a cost-effective means of improving crop yield in small garden spaces. Given the renewed interest, big box stores have begun stocking copper-wrapped dowels as a means of improving plant growth in urban container gardens, yet whether such passive electroculture is sufficiently beneficial to plant growth to justify the cost and materials, particularly of copper, remains debated. It is likely that copper rods produce too little voltage to affect plant physiology. In this study, we tested the hypotheses that 1) inserting copper-wrapped dowel rods into the soil will not improve plant growth, photosynthesis, or yield, and 2) if copper-wrapped dowel rods improve plant growth, it is due to copper fertilization rather than electrical conductance. We tested these hypotheses on two leafy green vegetables, mustard greens and kale, and two root vegetables, beets and turnips, to determine if plant life history was an important factor in the efficacy of passive electroculture. We found no consistent evidence that passive electroculture is beneficial to crop growth or yield in container gardens. Although we documented statistically significant effects of buried copper on the above- and belowground biomass of turnips, it is unlikely that improved turnip yield was due to copper fertilization because plants grown with exposed copper rods did not show the same effect. While crop production could potentially be enhanced by the application of active electrical fields, the voltages required exceed what is produced by copper-wrapped wooden dowels. We therefore suggest that both the production and purchase of such products would waste both financial and natural resources.